2012
DOI: 10.1074/jbc.m112.370601
|View full text |Cite
|
Sign up to set email alerts
|

Calcyon Forms a Novel Ternary Complex with Dopamine D1 Receptor through PSD-95 Protein and Plays a Role in Dopamine Receptor Internalization

Abstract: Background: Calcyon has been associated with various dopamine D 1 receptor signalings despite no direct interaction between them. Results: Calcyon forms a novel ternary complex with D 1 DR through PSD-95. Conclusion: Calcyon, by forming a ternary complex, regulates D 1 DR internalization in a phosphorylation-dependent manner. Significance: Regulation of dopaminergic signaling by calcyon⅐PSD-95⅐D 1 DR complex may represent a novel target for related neuropsychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Finally, the interaction between dopamine and glutamate neurotransmission can be mirrored by the modulation of molecules belonging to synaptic plasticity pathways, such as PSD-95, that is modulated by antipsychotics [125,126] and by selective blockade of D2 receptors [127]. PSD-95 in turn regulates D1 receptor trafficking and internalization [128,129] and inhibits D1-NMDA receptor coupling [130].…”
Section: Dopamine-glutamate Interplay At the Psd And Mirna Dysfunctiomentioning
confidence: 98%
“…Finally, the interaction between dopamine and glutamate neurotransmission can be mirrored by the modulation of molecules belonging to synaptic plasticity pathways, such as PSD-95, that is modulated by antipsychotics [125,126] and by selective blockade of D2 receptors [127]. PSD-95 in turn regulates D1 receptor trafficking and internalization [128,129] and inhibits D1-NMDA receptor coupling [130].…”
Section: Dopamine-glutamate Interplay At the Psd And Mirna Dysfunctiomentioning
confidence: 98%
“…Ca 2+ plays an important role not only in signaling pathways causing the activation of proteins such as protein kinase calcium-dependent (PKC) but also in the modulation of neurotransmitters release by exocytosis. It has been shown that this particular signaling pathways occurs primary in the prefrotal cortex and calcyon has been found co-localize with D1Rs in the dendritic spines on the pyramidal neurons [31]. The activation of this pathway in the medial prefrontal cortex is involved in impulsive choice in rats and neuropsychiatric disorders [32], in fact up-regulation of the interaction of calcyon and D1Rs has been found in schizophrenic patients [33].…”
Section: Aging and Disease • Volume 6 Number 5 October 2015 352mentioning
confidence: 99%
“…Out of the latter, calcyon density in SN was noted to be particularly high (Oakman and Meador-Woodruf, 2004). Furthermore, calcyon forms a ternary complex with D1 dopamine receptor (D(1)DR1) and thus regulates D(1)DR trafficking (Ha, 2012). Calcyon may also have a potential role as a partner of clathrin light chains implicated in endocytosis and synaptic plasticity in PD (Xiao, 2006, Heijtz, 2007).…”
Section: Discussionmentioning
confidence: 99%